2011
DOI: 10.1016/j.ajhg.2010.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of Dense Genecentric Association Studies Reveals Common and Uncommon Variants Associated with Height

Abstract: Height is a classic complex trait with common variants in a growing list of genes known to contribute to the phenotype. Using a genecentric genotyping array targeted toward cardiovascular-related loci, comprising 49,320 SNPs across approximately 2000 loci, we evaluated the association of common and uncommon SNPs with adult height in 114,223 individuals from 47 studies and six ethnicities. A total of 64 loci contained a SNP associated with height at array-wide significance (p < 2.4 × 10(-6)), with 42 loci surpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
84
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(87 citation statements)
references
References 39 publications
3
84
0
Order By: Relevance
“…In the last decade, a hundred single-nucleotide polymorphisms (SNP) capable of influencing adult height were identified by genome-wide association studies, including SNPs located near to NPR3 and NPPC genes . Four SNPs (rs2679178, rs749052, rs2580816, rs6717918) located upstream of NPPC and five SNPs surrounding the NPR3 gene (rs6450922, rs1173727, rs3792752, rs10472828, rs10472828) were related to adult height [2,3,4,5,6,7]. Each variant allele was associated with an estimated mean change of around 0.4 cm in height.…”
Section: Polymorphisms In Natriuretic Peptide System and Normal Heighmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last decade, a hundred single-nucleotide polymorphisms (SNP) capable of influencing adult height were identified by genome-wide association studies, including SNPs located near to NPR3 and NPPC genes . Four SNPs (rs2679178, rs749052, rs2580816, rs6717918) located upstream of NPPC and five SNPs surrounding the NPR3 gene (rs6450922, rs1173727, rs3792752, rs10472828, rs10472828) were related to adult height [2,3,4,5,6,7]. Each variant allele was associated with an estimated mean change of around 0.4 cm in height.…”
Section: Polymorphisms In Natriuretic Peptide System and Normal Heighmentioning
confidence: 99%
“…Studies in twins have indicated that the heritability of height is high (∼80%), suggesting that genetic variation is the main determinant of stature [1]. Although rare genetic variants are involved with larger effects on stature, common polymorphisms are significantly associated with height in healthy individuals [2]. Among the identified genes associated with stature, there are several genes that act in the growth plate-promoting endochondral ossification [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the C allele of rs2282978 (CDK6) and rs2871865 (IGF1R) , the A allele of rs2425019 (MMP24) and the T allele of rs8081612 (MAP3K3) and rs3782415 (SOCS2) were among the SNPs most strongly associated with adult height in Europeans [8,9,10]. Moreover, rs2425019 (MMP24) , rs8081612 (MAP3K3) , rs2871865 (IGF1R) and rs3782415 (SOCS2) were also associated with children's and adolescents' height in other populations (table 1).…”
Section: Introductionmentioning
confidence: 99%
“…In normal individuals adult height is affected by a large number of genes and normal growth hormone (GH) secretion is highly variable [1,2,3]. Growth disorders resulting in short stature arise from a spectrum of different aetiologies including hormone deficiencies, hormone resistance, nutritional insufficiency, chronic disease (e.g.…”
Section: Introductionmentioning
confidence: 99%